2021
DOI: 10.1038/s41598-021-83859-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hydrogen trapping at second phase particles in zirconium alloys

Abstract: Zirconium alloys are used in safety–critical roles in the nuclear industry and their degradation due to ingress of hydrogen in service is a concern. In this work experimental evidence, supported by density functional theory modelling, shows that the α-Zr matrix surrounding second phase particles acts as a trapping site for hydrogen, which has not been previously reported in zirconium. This is unaccounted for in current models of hydrogen behaviour in Zr alloys and as such could impact development of these mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In zirconium, deuterium was found to be localised around second phase particles (SPPs) in Zircaloy-2 and Zircaloy-4 (Figure 2), this had not previously been seen but this observation is important for understanding the degradation of these alloys due to hydrogen ingress during service [5].…”
mentioning
confidence: 75%
“…In zirconium, deuterium was found to be localised around second phase particles (SPPs) in Zircaloy-2 and Zircaloy-4 (Figure 2), this had not previously been seen but this observation is important for understanding the degradation of these alloys due to hydrogen ingress during service [5].…”
mentioning
confidence: 75%
“…When the hydrogen concentration exceeds its solubility limit, embrittle hydrides will precipitate in the matrix of zirconium and lead to the degradation of mechanical properties of the claddings, which has negative effects on the service life of zirconium alloys and the safe operation of reactors. The interaction between hydrogen and metal, which involves the adsorption and dissociation reaction of hydrogen on metal, has been a crucial research subject in the past decades. Many studies reported the zirconium–hydrogen interaction mechanism in terms of conventional experimental and theoretical computational approaches. All of these suggest that an in-depth study of zirconium–hydrogen interactions is essential to predict the service performance of zirconium alloys and to assess the safe operation of nuclear fuel components.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of hydrogen-related phenomena is limited due to the difficulties of detecting and imaging hydrogen with conventional electron and X-ray based techniques (Meyer et al, 2008). Methods used to detect and quantify hydrogen include nanoscale secondary ion mass spectrometry (Li et al, 2020; Jones et al, 2021), time-of-flight secondary ion mass spectrometry (Jiang et al, 2020), and optical emission spectroscopy techniques, such as laser-induced breakdown spectroscopy (Pardede et al, 2019; Kautz et al, 2021) and LECO hydrogen hot vacuum extraction (Ensor et al, 2017), but they have not yielded all of the necessary experimental data. Atom probe tomography (APT) has nanometer-level spatial resolution and high chemical sensitivity, making it a viable tool for hydrogen analysis.…”
Section: Introductionmentioning
confidence: 99%